Conformational Changes Induced by S34Y and R98C Variants in the Death Domain of Myd88 - Gosu, Vijayakumar; Won, KyeongHye; Oh, Jae-Don; Shin, Donghyun (Frontiers in Molecular Biosciences, 2020)
Myeloid differentiating factor 88 (Myd88) is a universal adaptor protein that plays a critical role in innate immunity by mediating TLR downstream signaling. Myd88 death domain (DD) forms an oligomeric complex by association with other DD containing proteins such as IRAK4. Despite its universal role, polymorphisms in Myd88 can result in several deadly diseases. Previous studies have suggested that, out of several non-synonymous single nucleotide polymorphisms (nsSNPs), the variants S34Y and R98C in the DD of Myd88 disrupt the formation of the Myddosome complex. Therefore, we performed molecular dynamic (MD) simulations on wild-type (Myd88WT) and mutant (Myd88S34Y, Myd88R98C) DDs to evaluate the subtle conformational changes induced by these mutations. Our results suggest that the S34Y variant induces large structural transitions compared to the R98C variant as evidenced by residual flexibility at the variable loop regions, particularly in the H1-H2 loop, and variations in the collective modes of motion observed for wild-type and mutant Myd88 DDs. The residue interaction network strongly suggests a distortion in the interaction pattern at the location of the mutated residue between the wild-type and mutants. Moreover, residue betweenness centrality values indicate that variations in the distribution of functionally important residues may be reflected by distinct residue signal transductions in both wild-type and mutant Myd88 DDs, which may influence the interaction with other DDs in TLR downstream signaling.